2016
DOI: 10.1002/hed.24643
|View full text |Cite
|
Sign up to set email alerts
|

Correlative study of dose to thyroid and incidence of subsequent dysfunction after head and neck radiation

Abstract: Achieving D <50 Gy, V <50%, and mean dose <54.58 Gy during RT planning may decrease the incidence; whereas female sex and concurrent chemotherapy seem to increase the risk of RT-induced hypothyroidism. © 2016 Wiley Periodicals, Inc. Head Neck 39: 548-554, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 34 publications
(114 reference statements)
5
41
1
5
Order By: Relevance
“…Studies have investigated the risk factors for RT-related HT in NPC patients, and reported similar results as our univariate analysis, including female sex, 11 younger age, 12 smaller pretreatment thyroid-gland volume, 13,14 high mean radiation dose, 4,15 and high minimum radiation dose. 7 Taking the relatively high correlation among mean radiation dose, minimum radiation dose, and DVH parameters into account, we did not include a mean radiation dose or minimum radiation dose into the multivariate analysis, and found the combined DVH constraints to be independent prognostic factors for HT.…”
Section: Discussionsupporting
confidence: 80%
“…Studies have investigated the risk factors for RT-related HT in NPC patients, and reported similar results as our univariate analysis, including female sex, 11 younger age, 12 smaller pretreatment thyroid-gland volume, 13,14 high mean radiation dose, 4,15 and high minimum radiation dose. 7 Taking the relatively high correlation among mean radiation dose, minimum radiation dose, and DVH parameters into account, we did not include a mean radiation dose or minimum radiation dose into the multivariate analysis, and found the combined DVH constraints to be independent prognostic factors for HT.…”
Section: Discussionsupporting
confidence: 80%
“…Various reports highlight a 20 to 50% incidence of post-radiation primary hypothyroidism after neck irradiation, 11,12 likely dependent on the dose of radiation delivered to the thyroid bed. 13 The incidence and sequelae of radiation-induced hypothyroidism in the head and neck cancer survivor are significant, and routine screening of thyroid function is recommended in the National Comprehensive Cancer Network (NCCN) guidelines. 14 The effects of radiation on the pituitary gland are also well described, with evidence of dose-dependent pituitary insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest mean dose at which thyroid dysfunction was seen, was at 4804cGy. In the study by Ling et al 31 the lowest mean dose at which thyroid abnormality occurred was noted to be at 29.8 Gy. In the study by Kim et al 7 there was a positive correlation between higher mean dose to the thyroid and thyroid dysfunction.…”
Section: Discussionmentioning
confidence: 92%